ANALISIS PANGSA PASAR MOBIL TOYOTA AVANZA DI KUTAI TIMUR - Mardiana, Edy Fatmaraga, Theresia Militina (EKONOMIA, 2016)
The purpose of this study is to determine the market share of car brands Toyota Avanza and knowing the type of the largest market share in 2013 in East Kutai.The results of this study stated hypothesis proposed that "alleged that the market share of car brands Toyota Avanza types from January to December in 2013 is larger than its competitors in the East Kutai Regency" is denied, the reason for this hypothesis is rejected Car Market Share brands Toyota types Avanza from January to December of 2013 is smaller than the main competitor brand cars Daihatsu Xenia types in East Kutai.Market share (market share) was achieved by the type of car car brand Toyota Avanza types in East Kutai Regency pretty good. This is evident from market share gains from January to December in 2013 an estimated market share (market share) for the car brand Toyota Avanza is kind of 30.63%. It shows that for the car brand Toyota Avanza types dominate the market only amounted to 30.63% or second order compared with the type of cars that are in the East Kutai.Type of car brands Toyota Avanza types able to compete with other types of cars both from the point of price, quality and consumer tastes factors, sales of this car is influenced by three factors. Aside from the related factors of factors campaign carried out by the national manufacturers are also very influential on the sale of this issue.